Impact of age and retinal degeneration on the light input to circadian brain structures - Lupi, D; Semo, M; Foster, R (2012)
Aging causes anatomical and functional changes in visual and circadian systems. In wild type mice rods, cones, and photosensitive retinal ganglion cells (pRGCs) decline with age. In rd/rd cl mice, the early loss of rods and cones is followed by protracted transneuronal loss of inner retinal neurons as well as the pRGCs. Here we use Fos induction to study the light input pathway to the suprachiasmatic nuclei (SCN), the intergeniculate leaflets (IGL) and ventral lateral geniculate nuclei (vLGN) of old (~700 days) and young (~150 days) wild type and rd/rd cl mice. Cholera toxin tracing was used in parallel to study the anatomy of this pathway. We find that aging rather than retinal degeneration is a more important factor in reducing light input to the SCN, causing both a reduction in Fos expression and retinal afferents. Furthermore, we show light-induced Fos within the vLGN and IGL is predominantly subserved by rods and cones, and once again aging reduces the amplitude of this response. © 2012 Elsevier Inc.